VALIDITAS BAHAN AJAR ZERO START BERBASIS DEEP LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V SD - Puspitaningrum, Mareeta Nara; Danuri, Danuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study centers on the creation and validation of a deep learning-integrated instructional resource titled "Zero Start," specifically designed for 5th-grade students tackling whole numbers up to 100,000. The research is driven by the prevalence of low mathematical conceptual mastery and a lack of innovative pedagogical tools in schools, which often diminishes student confidence when facing abstract topics. Adopting the Research and Development (R&D) framework via the ADDIE model, this project focused on the Development phase to ascertain product feasibility through expert appraisal. Evaluation results yielded a 90% score from media specialists and 92.5% from subject matter experts. With a cumulative average of 91.25%, categorized as "Excellent," "Zero Start" is verified as a highly viable learning medium to bolster students' numerical competence.